The Difference in the Effect of Using Fins and Zoomers on the Improvement of 50-Meter Backstroke Swimming Speed - Annisa Lintang; Supriyono (Universitas Negeri Semarang, 2025)
This study was conducted to examine the extent to which the use of fins and zoomers affects the improvement of 50-meter backstroke swimming speed among athletes of the Tri Cakti Semesta Semarang Club. A quantitative approach with a two-group pretest-posttest design was used. Twenty athletes were selected as participants and divided into two groups: the first group trained using fins, while the second group trained with zoomers. Data were collected through swimming speed tests conducted before and after 16 training sessions. The results were analyzed using Paired Samples T-Tests and Independent Samples T-Tests. The findings showed that both fins and zoomers significantly improved athletes' 50-meter backstroke swimming performance, with an average increase of 0.69 seconds and 0.72 seconds, respectively. However, a comparative analysis did not show a significant difference between the two training methods. In conclusion, both tools can be considered equally effective as training variations to support the improvement of backstroke swimming performance.